Nurses’ Experiences of Caring for Patients With Suspected or Confirmed COVID-19 in the Initial Stage of the Pandemic - Janet Mattsson PhD, RNA; Elin Hedlund BSc, RN; Lisa George-Svahn MSc, RN; Elina Scheers-Andersson PhD, MSc; Monir Mazaheri PhD, RN; Gunilla Björling PhD, RN (SAGE Open Nursing, 2022)
Introduction Nursing staff have faced various challenges during the global pandemic of COVID-19 such as nursing shortages. The great number of COVID-19 patients requiring hospitalization placed heavy demands on healthcare staff to maintain patient safety and to work according to constantly changing guidelines to prevent the spread of infection. Objective The objective was to describe nurses’ experiences of caring for patients with suspected or confirmed COVID-19 in the initial phase of the pandemic. Methods The study has a qualitative design. Semi-structured interviews were conducted with seven nurses in primary care and hospital care during the initial stage of the pandemic. Qualitative content analysis with an inductive approach was used. Results The nurses expressed that the working routines changed very quickly at the onset of the pandemic. A triage system was implemented to care for patients with symptoms of COVID-19 to prevent transmission between patients. A major change was the constant use of personal protective equipment in patient care. The nurses also experienced a sense of inadequacy regarding the care of the patients and became emotionally affected and exhausted. Conclusion The nurses experienced that many patients worsened clinically, leading to exhausting and difficult nursing care situations. They also experienced increasing responsibility since new protective equipment and procedures needed to be quickly implemented according to frequently changing recommendations, causing the nurses to feel uncertain about how to maintain patient safety. Support from colleagues was crucial to cope throughout the initial stage of the pandemic.